The Christmas birth : When God came to Earth. - Rogers, Elaina (United States of America, Book1One Publishing, 2014)
The story of the birth of Christ, set completely to rhyme. It will draw your child in with the whimsical pictures and wording...a much needed reminder of the true meaning of Christmas!
Alumni Author